The Roman Catholic Controversy Catholics & Protestants - Do the Differences Still Matter? - White, James R. (James Robert) (Minneapolis, Minn. Bethany House Publishers, 1996)
Discusses the relationship between Evangelicals and Roman Catholics covering the social and moral issues on which they agree and their differences on theological issues.
Keywords: Catholic Church